Fibrinogen-to-albumin ratio percentage: An independent predictor of disease severity and prognosis in anti-N-methyl-D-aspartate receptor encephalitis - Du, Juan; Shao, Yingzhe; Song, Yajun; Wang, Kaixin; Yang, Xuan; Li, Yanfei; Yao, Yaobing; Gong, Zhe; Jia, Yanjie (Frontiers in Neurology, 2023)
Purpose This retrospective study aimed to investigate the relationship between fibrinogen-to-albumin ratio percentage (FARP) and disease severity and prognosis in patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. Methods Medical records and clinical characteristics from 181 patients with anti-NMDAR encephalitis were included. The modified Rankin Scale (mRS) was used to analyze disease severity and prognosis at admission and discharge, and correlations between FARP, disease severity, and prognosis were analyzed. Receiver operating characteristic (ROC) curves were used to evaluate the efficiency of FARP in assessing disease severity and prognosis. Results Compared to the control group, patients with anti-NMDAR encephalitis had higher fibrinogen (Fib) levels (P < 0.001), neutrophil counts (P < 0.001), and FARP levels (P < 0.001) but had lower albumin levels (P = 0.003). The enrolled patients were divided into mild-to-moderate and severe groups according to their mRS scores both at admission and discharge. FARP levels were significantly elevated in the severe group compared to the mild-to-moderate group among patients with anti-NMDAR encephalitis both at admission and discharge (admission 6.0 vs. 7.40, P < 0.001; discharge 6.43 vs. 8.18, P<0.001). Indeed, the mRS scores at admission (56 vs. 26%, P < 0.001) and discharge (26 vs. 11%, P = 0.006) in the high FARP group were significantly higher than those in the low FARP group. Furthermore, FARP was positively correlated with the mRS scores at admission (r = 0.383, P < 0.001) and discharge (r =0.312, P < 0.001). In the multivariate analysis, FARP was significantly associated with disease severity (odds ratio [OR] = 1.416, 95% confidence interval [CI] = 1.117-1.795, P = 0.004) and prognosis (OR = 1.252, 95% CI = 1.010-1.552, P = 0.040). FARP-based ROC curves predicted disease severity, with a sensitivity of 0.756, a specificity of 0.626, and an area under the ROC curve of 0.722 (95% CI = 0.648–0.796, P < 0.001*). The ROC curve predicted the disease prognosis with a sensitivity of 0.703, a specificity of 0.667, and an area under the ROC curve of 0.723 (95% CI = 0.629–0.817, P < 0.001*). Conclusion Our results indicate that FARP is a novel predictive marker for disease severity and prognosis of anti-NMDAR encephalitis.